Supervisors’ assessment practices: implications for diploma level student teachers’ learning during teaching practice - Mpate, Hawa (Papers in Education and Development, 2024)
This study explored the implications of supervisors' assessment practices for student teachers' learning during teaching practice in Moshi Rural District, Kilimanjaro. A qualitative approach, informed by a multiple case study design, was employed. Data were collected from 19 participants, including five supervisors (tutors), six student teachers from a diploma teacher training college, five mentor teachers, and three school heads across three public secondary schools. Interviews, focus group discussions (FGDs), classroom observations, and document analysis were employed to collect data. The findings revealed various assessment practices used by supervisors and their implications for student teachers' learning during teaching practice. While some practices were effective, others were poorly organised, untimely, and of low quality—characterised by rushed, overly objective, grade-focused, and inconsistent evaluations. Supervisors also faced constraints such as limited time and financial challenges, hindering effective assessment. The study recommends that teacher training colleges strategically time assessments to align with key milestones in the student teaching experience.